Cover Feature: Supramolecular Alloys from Fluorinated Hybrid Tri4Di6 Imine Cages (Chem. Eur. J. 33/2021). Issue 33 (27th May 2021) - Kunde, Tom; Pausch, Tobias; Schmidt, Bernd M.
Abstract : Eight hybrid Tri 4 Di 6 imine cages with a tuneable degree of fluorination and one fully fluorinated Tri 4 Di 6 imine cage are formed by [4+6] dynamic imine condensation in solution. These cages with unlimited miscibility in the solid state were obtained as highly crystalline samples after recrystallization and even showed retention of the crystal lattice, forming essentially organic cage alloys mixing fluorinated and non‐fluorinated building blocks, depicted as golden honeycomb‐like structure. More information can be found in the Communication by B. M. Schmidt et al. (DOI: 10.1002/chem.202100891 ).